Knowledge of Snake Bite Management among Farmers - Fazah Nur Alif Fathur Rahmah; Zhafira Puspitarini; Tiara Aprilia Riyanti; Enggal Hadi Kurniyawan; Dicky Endrian Kurniawan; Alfid Tri Afandi; Kholid Rosyidi Muhammad Nur; Leni Agustin (KHD Production, 2025)
Snakebite is a global emergency that can result in death, especially among farmers. Knowledge of snakebite management for farmers can improve first aid skills and abilities. This study aims to analyze the importance of snakebite management on farmer safety. The method used in this research is a literature study by finding articles in 3 databases: Google Scholar (3,000 articles), Pubmed (4 articles), and ScienceDirect (196 articles). After that, the journals were sorted again with more specific keywords and years that met the criteria (2019-2024). The search keywords use two languages: the English keywords use